Trabalho na experiência de travestis e mulheres trans - Souza, Gabriela da Rocha (2022)
In the current model of social organization, there is the dominant phenomenon called cisheteronormativity, that is, cisgenderness and heterosexuality are conceived as natural, correct, healthy and expected. In short, as the only ways to live and experience gender identity and sexual orientation. Thus, the standards of gender and sexuality that deviate from this norm are referred to processes of exclusion, discrimination and various other oppressions, in the case of the LGBTI community (lesbians, gays, bisexuals, transvestites, transsexuals and/or transgender and intersex). This occurs, above all, with people who are most at odds with gender norms, transvestites and trans women, on whom the worst rates of unemployment and violence fall. Generally, this group suffers frequent and early expulsion from the family, they are expelled directly or indirectly from school and are constantly excluded from formal job opportunities, factors that contribute to the social vulnerability they experience. The work here is understood not only as a means of material survival, but also as an activity loaded with symbolic value that is fundamental to the identity, subjective and social construction of the subjects. The main objective of this research is to understand the representations of transvestites and trans women about transphobia, especially in relation to work and the search for survival. For this, with the qualitative method, semi-structured interviews were carried out with transvestites and trans women who had professional experiences and a bibliographic survey on this topic. Through the interviews, it was possible to perceive that all of them have experiences with transphobia since childhood and their professional trajectories were often related to informality, prostitution and specific areas of the beauty market. Only one interviewee had significant experiences with formal employability. As much as brazilian society has advanced in guaranteeing some rights for the LGBTI+ community, transvestites and trans women are still the most vulnerable in this group, since they face prejudice on a daily basis and are targets of violence in different areas of social life.